SCREENING FOR DIABETIC RETINOPATHY AND PROPTOSIS TO PREVENT BLIND IN JERO MANGKU CULTURE INTARAN VILLAGE, WEST SANUR - Noviantari, I Gusti Agung Ratna; Suryathi, Ni Made Ari; Suryanadi, Ni Made (Majalah Oftalmologi Indonesia, 2023)
Introduction and Objective: The social service of diabetic retinopathy (DR) and proptosis screening by going directly to the community is one of the efforts to reduce blindness. The aim of this study is reporting the result of DR and proptosis screening toward priests in Intaran Village, Sanur Kauh, Bali. Method: This is an observational study with cross-sectional approach conducted in April 2022.We performed DR screening using portable funduscopy and proptosis screening using Herthel exophthalmometry. Collected data were analyzed descriptively. Results: In the diabetic retinopathy screening, a total of 8 participants had their eyes examined. Based on the results of the examination, 3 people and 5 eyes were found to have diabetic retinopathy. Of the 3 participants who had RD, two participants had bilateral RD, while 1 had unilateral RD. Of the 5 eyes that had RD, four eyes had a mild degree, while 1 eye had a moderate degree. None of the eyes had severe degrees. Participants with RD were given referrals for further treatment. The average Hertel exophthalmometry examination result in the right eye was 14.30 ± 2.14 mm while in the left eye was 14.46 ± 2.11 mm. This data can be used as a reference for normal values in the population. Conclusion: DR screening is important because it can detect the disease before the appearance of complaints. DR screening by going directly to the community can also reach people who have difficulty in accessing health care facilities.